Advances in the role of a plant coagulant (Cynara cardunculus) in vitro and during ripening of cheeses from several milk species - Sousa, Maria José (2011)
Extracts from dried flowers of Cynara cardunculus have been employed successfully for many centuries in Portugal and some regions of Spain for the manufacture of traditional cheeses. Several studies have been performed in vitro and in actual cheeses focusing on the activity and specificity of proteinases from C. cardunculus, in attempts to further characterise this plant coagulant as a proteolytic agent in cheese ripening. In vitro studies encompassed extraction conditions, storage of extracts, proteolysis and specificity on caseins using experimental conditions that parallel milk and cheese during ripening. In vivo studies encompassed the effect of the type of milk (bovine, ovine and caprine) in terms of proteolysis, specificity of those plant proteinases during ripening, comparison of microbiological, chemical, proteolytic and lipolytic characteristics in ovine milk cheeses relative to animal rennet counterparts, and effect of native microflora, thermal processing and addition of starter cultures in ovine cheeses